Schizobasis litanthiflora (Hyacinthaceae, Urgineoideae), a new species from the Tugela River Basin of KwaZulu-Natal, South Africa - Crouch, Neil R.; Martínez-Azorín, Mario (Phytotaxa, 2024)
In the course of a taxonomic revision of Schizobasis, field work in the KwaZulu-Natal Province of South Africa revealed plants showing a distinct syndrome of morphological characters not previously reported in the genus, especially regarding the long lasting, nodding, consistently tubular-like, constricted flowers, which resemble those of its phylogenetically sister genus Litanthus. Historical herbarium records of Schizobasis in KwaZulu-Natal, although limited, support the description of Schizobasis litanthiflora as a new disjunct species. We provide a complete morphological description of the new taxon, as well as data on its ecology and distribution.